GAYA HIDUP KAITANNYA DENGAN KEPUTUSAN KONSUMEN DALAM MEMBELI MINUMAN KOP - Yulianti, Yanti; Deliana, Yosini (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2018)
This study aims to determine lifestyle ofNoah's Barn’s consumer, the process of consumer purchase decision, and to find out how much influence of lifestyle on consumer decisions in Noah's Barn. The type of study used in this study is quantitative by survey method. The population used in this study is all consumers who visited Noah's Barnand 100 respondents selected usingsystematic random sampling.The analysis technique used is simple linear regression. The results of the study showed that lifestyle variables have positive and significant influence on purchasing decisions in Noah's Barn’s consumer. Lifestyle variable is able to explain the variance of purchasing decision equal to 32,1% and the residue equal to 67,9% is influenced by other variables was not examined in this study.